ChemInform Abstract: Identification and Biological Evaluation of Flavonoids from the Fruits of Prunus mume. Issue 33 (19th August 2014) - Yan, Xi‐Tao; Li, Wei; Sun, Ya‐Nan; Yang, Seo‐Young; Lee, Sang‐Hyun; Chen, Jian‐Bo; Jang, Hae‐Dong; Kim, Young‐Ho
Abstract isolation and structure determination of potent antioxidant and antiostereoporosis compounds including the novel flavan dimer (I)